COMPARISON OF ADDITIVE PROTECTIVE LAYER ON THE CYLINDER LINER SURFACE USING DIESEL ENGINE AND PIN-ON-PLATE TEST RIGS - Bektas, D.; Kaleli, H. (SCIBULCOM LTD, 2011)
In this research, the layer formation of additives on the surface of cylinder liner (single cylinder Diesel engine liner operated 22 h) was examined by using binocular, optical, scanning electron microscope and energy dispersive X-ray spectra and was compared to the plates tested in reciprocating pin-on-plate tribotest machine. The additive materials such as Ca, Zn, P, and S displayed a significant presence in top dead center (TDC), but relatively less so in middle center (MC) and no additive elements were found in the bottom dead center (BDC). Six plates (A, B, C, D, E and F) were tested in tribotest machine and some of them showed surprisingly similar results on their rubbed surfaces as in cylinder liner of Diesel engine during microscopic examination. Additives were detected as islands both in Diesel engine cylinder liner and tested plates. Almost the same additives such as Ca, Zn, P and S were detected in plates A and B as well as in Diesel engine TDC and MC. Plate C revealed also the presence of P and S elements. Most of the machining marks still remained on the surface of cylinder liner and plates.
Keywords: engine cylinder liner; plates; additive layer; microscopic surface examination; LUBRICATION; WEAR; Engineering